Identifikasi Interval Melodi Lagu Aneuk Yatim Ciptaan Rafly Kande - Surya Rahman; Rico Gusmanto (Institut Seni Indonesia Padangpanjang, 2021)
Aneuk Yatim is a Aceh Pop song created by Rafly who is a member of the Kande Group. This group creates songs using lyrics, characters, and Aceh music instruments. The vocals of this song consist of three parts, where each part has antecedents and consequent sentences or what is known as question sentences and answer sentences. Each sentence of the song has a measurable interval. In western music theory, the intervals are in the order of Prime, Second, Terts, Quart/Kwart, Quint/Kwint, Sekt, Septim, None, Decim, Undecim, Dodecim, and Tredecim. Then, this study identifies the use of intervals using western music theory in studying and analyzing each part of the Aneuk Yatim song by Rafly Kande. This study uses a qualitative method with stages in the form of data reduction, data presentation, and looking of conclusions. Data analysis was carried out with an interactive model as a way to looking the conclusions and verify all things contained in the reduction and presentation of the data when data collection ended. The purpose of this study is to identify more deeply the tune intervals in the melody in each part of music. The result of this research is to know the shape of the interval of each melodic journey of the Aneuk Yatim song.Keywords: Aneuk Yatim; Interval; Melody; Rafly KandeABSTRAKLagu Aneuk Yatim adalah lagu Pop Aceh ciptaan Rafly yang tergabung dalam Grup Kande. Grup ini menciptakan karya lagu menggunakan lirik, karakter, dan penggunaan instrumen musik Aceh. Vokal lagu ini terdiri dari tiga bagian, dimana setiap bagian memiliki kalimat antecedents dan consequents atau yang dikenal dengan kalimat tanya dan kalimat jawab. Setiap kalimat lagu memiliki interval atau jarak nada yang dapat diukur. Dalam teori musik barat, interval tersebut memiliki urutan antara lain Prime, Second, Terts, Quart/Kwart, Quint/Kwint, Sekt, Septim, None, Decim, Undecim, Dodecim, dan Tredecim. Dengan demikian, penelitian ini mengidentifikasi penggunaan interval dengan menggunakan teori musik barat dalam mengkaji dan menganalisis setiap bagian pada lagu Aneuk Yatim karya Rafly Kande. Penelitian ini menggunakan metode kualitatif dengan tahapan berupa reduksi data, penyajian data, dan penarikan kesimpulan. Analisa data dilakukan dengan model interaktif sebagai cara untuk menarik kesimpulan dan verifikasi atas semua hal yang terdapat dalam reduksi dan sajian datanya ketika pengumpulan data berakhir. Tujuan dari penelitian ini adalah mengidentifikasi lebih dalam mengenai interval nada pada melodi dalam sebuah karya musik. Hasil dari penelitian ini adalah mengetahui bentuk jarak nada dari setiap perjalanan melodi dari lagu Aneuk Yatim.Kata Kunci: Aneuk Yatim; Interval Nada; Melodi Lagu; Rafly Kande